Desain dan Implementasi Aplikasi Monitoring Tender Berbasis Excel Visual Basic di PT XYZ - Fitriawan, Anisa; Chaniago, Harmon (Fakultas Teknik, Universitas PGRI Banyuwangi, 2025)
The Marketing and Sales Division of PT XYZ faces challenges in managing tender data due to the lack of an integrated and structured system. The dispersion of data across multiple locations complicates the monitoring process, particularly when the company participates in multiple tenders simultaneously. This project aims to address the issue by identifying initial problems, designing, and implementing a tender monitoring application within the division. The development process employed the waterfall methodology. Data were collected through direct observation and interviews with administrative staff as primary sources, while secondary data were obtained from relevant documentation. The results showed that the administrative staff in the marketing and sales division were significantly assisted in managing tender data, particularly in terms of processing speed. Previously, data management was performed manually using Excel documents without automation, taking around 10 minutes. After the implementation of this application, the tender data processing time was significantly reduced, with an average speed improvement of 89%. This solution contributes to enhancing the efficiency, structure, and accuracy of tender information management, facilitates progress monitoring, and supports the creation of tender reports within the Marketing and Sales Division of PT XYZ.